Religious Architecture in Crete: Materiality and Identities between the Venetian and the Ottoman Rule - Lorenzon, Marta (Journal of Greek Archaeology, 2018)
In archaeology, the concept of identity is investigated with a clear focus on material culture, while architecture has often been excluded from this narrative, or when included, the general outlook gravitates towards more contemporary case studies. This article argues that iconoclasm, cultural appropriation and architectural destruction are not issues only concerning the recent past, but they are a diachronic phenomenon present endemically in a variety of case studies that pertain to archaeological contexts.